Pengaruh Akuntansi dan Teknologi Informasi terhadap Kualitas Laporan Keuangan UMKM Sektor Kuliner di Kota Padang - Umar, Desyani; Ayu, Sinta Gusti; Rivandi, Muhammad; Kartika, Elvirha Dwi (Jurnal Akuntansi & Keuangan Unja, 2026)
This study aims to analyze the effect of accounting understanding and information technology on the quality of financial reports of MSMEs in the culinary sector in Padang City. The research method used is quantitative research with a survey approach. The data used are primary data obtained through the distribution of questionnaires to MSME actors in the culinary sector in Padang City. The research population consisted of 15,830 business units, with the sampling technique using purposive sampling, resulting in 90 respondents. The data analysis techniques used include instrument testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination test using the SPSS program. The results of the study indicate that accounting understanding has a positive and significant effect on the quality of MSME financial reports, while information technology does not have a significant effect on the quality of financial reports. This study implies that strengthening basic manual accounting competencies for culinary MSME actors is more urgently needed by stakeholders than merely focusing on digitalization, considering that the use of technology has not provided a significant contribution to the quality of financial reporting without a strong foundation in accounting understanding.